(untitled) (Theatrum historiae, 2019)
The aim of the study is to present the use of the popularity of John of Nepomuk at the time when he was newly proclaimed saint (1729), especially in the communication strategies of the Catholic and Lutheran clergy and ultimately in shaping the image of the royal representation through demonstrated relationships between the recatholized Wettins and the Habsburg imperial family. What is important here is not merely evidence supported by examples, but above all the imagination associated with them.